The Babylonian disputation poems: with editions of the series of the poplar, palm and vine, the series of the spider, and the story of the poor, forlorn wren - Jiménez, Enrique (Culture and history of the ancient Near East, 2017)
Â#x80;#x8E;Concordance between Lambertâ#x80;#x99;s and Kienastâ#x80;#x99;s Editionâ#x80;#x8E;Manuscripts and Origins; â#x80;#x8E;Characters and Storyline; â#x80;#x8E;Tradition and Genre; â#x80;#x8E;I.3.b.2. A Sumerian Forerunner?; â#x80;#x8E;I.3.c. Series of Ox and Horse; â#x80;#x8E;I.3.d. The Donkey Disputation; â#x80;#x8E;I.3.e. Nissaba and Wheat; â#x80;#x8E;Chapter I.4. The Place of Disputation Poems within Babylonian Literature; â#x80;#x8E;I.4.a. The Structure of the Disputations; â#x80;#x8E;Prologue; â#x80;#x8E;Disputation Proper; â#x80;#x8E;Adjudication Scene; â#x80;#x8E;I.4.b. The Style of the Disputation Poems; â#x80;#x8E;I.4.b.1. Verse and Style; â#x80;#x8E;I.4.b.2. Language Register; â#x80;#x8E;I.4.c. Literary Quotations